PENERAPAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN DAN HASIL BELAJAR SISWA KELAS IV A SD MUHAMMADIYAH 1 KETELAN SURAKARTA: SEBUAH PENELITIAN TINDAKAN KELAS - Rizki Rahma Kusuma; Natana Aunillah Naya; Riris Fatimah Nur Jannah; Choirun Nisa; Sri Martono Lanjar Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading comprehension is a fundamental skill that determines students' success in almost every subject, yet many fourth-grade students still struggle to understand the content of the texts they read. This classroom action research aimed to improve the reading comprehension skills and learning outcomes of 22 fourth-grade students at SD Muhammadiyah 1 Ketelan Surakarta through the application of sequential picture media (media gambar berseri). The study followed the Kemmis and McTaggart model, implemented in two cycles, each consisting of planning, action, observation, and reflection. Data were collected through reading comprehension tests administered before the intervention (pretest) and at the end of each cycle, supported by classroom observation. The results showed a steady improvement in the average score, from 57.95 in the pretest to 69.32 in Cycle I and 81.59 in Cycle II, with the percentage of students meeting the minimum mastery criterion (KKM) rising from 31.8% to 95.5%. The average normalized gain (N-Gain) reached 0.57, categorized as moderate. These findings indicate that sequential picture media effectively supports students in sequencing, predicting, and summarizing narrative content, thereby strengthening both reading comprehension and overall learning outcomes.